Profane death in burial practices of a pre-industrial society - Duma, Paweł (Archaeopress, 2019)
This book discusses phenomena characteristic of funeral practices of the pre-industrial society of Silesia (Poland). The author explores specific groups of people and the places they were interred, supplementing the study with analysis of the results of archaeological research, which mainly involved fieldwork carried out at former execution sites.